Recent advances in self-assembling peptide matrices as functional coatings for implantable devices - Tian, Yuan; Lu, Lei (Frontiers in Chemistry, 2022)
Nature has evolved numerous supramolecular machineries for modulating various cellular functions. Inspired by the assembly of these sophisticated structures in nature, the controlled assembly of synthetic peptides emerges as a promising approach to therapeutically relevant applications. The self-assembling biomimetic peptides could form well-ordered architectures through non-covalent interactions such as π-π stacking, van der Waals, electrostatic, and hydrogen bonding. In addition, the peptidic building blocks are highly biocompatible and allow facile chemical manipulation with diverse functionalities. For decades, a serious of engineered self-assembling peptides have been extensively studied as functional hydrogels for various applications. Meanwhile, the surface modification strategies based on self-assembling peptide matrices have also raised the attention of biomaterials researchers due to their programmability and 3D porous morphologies. This concise review will cover recent advances in self-assembling peptide matrices as functional coatings for implantable devices. The opportunities and challenges in this field will also be discussed.